2020
DOI: 10.3389/fonc.2020.01064
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA 103862 Promotes Proliferation and Invasion of Laryngeal Squamous Cell Carcinoma Cells Through the miR-493-5p/GOLM1 Axis

Abstract: Accumulating evidence suggests that circular RNAs (circRNAs) may be a key contributor to oncogenesis. Yet, the function of circRNAs in laryngeal squamous cell carcinoma (LSCC) is still not clear. In this study, we examined the function of circRNA_103862 in LSCC progression by analyzing the tissue specimens collected from a patient with LSCC by using different LSCC cell models in vitro and an LSCC xenograft model in nude mice. We found that circRNA_103862 was frequently upregulated in the tissues of LSCC and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Increasing evidence has shown that circRNAs play a crucial role in carcinogenesis, cancer progression, and clinical outcomes of various human cancers ( 19 ). For example, researchers found Circular RNA 103862 promoted proliferation and invasion of laryngeal squamous cell carcinoma cells through the miR-493-5p/GOLM1 axis ( 12 ). Besides, CircRNA_ACAP2 could suppress EMT in head and neck squamous cell carcinoma by targeting the miR-21-5p/STAT3 signalling axis ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has shown that circRNAs play a crucial role in carcinogenesis, cancer progression, and clinical outcomes of various human cancers ( 19 ). For example, researchers found Circular RNA 103862 promoted proliferation and invasion of laryngeal squamous cell carcinoma cells through the miR-493-5p/GOLM1 axis ( 12 ). Besides, CircRNA_ACAP2 could suppress EMT in head and neck squamous cell carcinoma by targeting the miR-21-5p/STAT3 signalling axis ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is the sixth most common type of human malignancy and involves carcinoma of several anatomic sites, such as lip, oral cavity, pharynx (nasopharynx, oropharynx, hypopharynx), and larynx, with an annual incidence of~600,000 per year (12,13). Although the diagnosis and treatment have advanced in recent years, HNSCC still has a high incidence and mortality rate in developing countries (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNA_103862 is highly expressed in the tumour tissues of LSCC. CircRNA_103862 regulates the expression of GOLM1 by interacting with miR-493-5p, and thus promotes proliferation and invasion of LSCC cells [16]. CircCORO1C acts as a sponge of let-7c-5p, and regulates its downstream gene PBX3 in LSCC, and CircCORO1C/let-7c-5p/PBX3 axis affects LSCC progression [17].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has suggested that the ceRNA pattern also works in LSCC progression. For example, circRNA_103862 promotes LSCC cell proliferation, migration, and invasion by the miR-493-5p/GOLM1 axis [36], while hsa_circ_0042666 promotes LSCC cell proliferation and invasion by the miR-223/TGFBR3 axis [37]. To further determine the biological functions of circPTK2, we analyzed its ceRNA mechanism in LSCC.…”
Section: Discussionmentioning
confidence: 99%